Digital skills and pronunciation of the English language of students of the UNMSM school of tourism administration, 2024 - Ramos Mendoza, Franci Maribel (2024)
The purpose of the research was to determine the relationship between digital skills and the pronunciation of the English language in Tourism Administration students at the Universidad Nacional Mayor de San Marcos in the year 2024. To achieve this objective, a quantitative study was carried out non-experimental design, in which surveys and questionnaires were used to evaluate digital skills, as well as evaluations to measure the level of language pronunciation. The sample was made up of 98 students out of a total of 103. The results showed that the use of digital skills significantly improves the pronunciation of the English language in the students. It was concluded that the relationship between digital skills and the pronunciation of the English language in UNMSM Tourism Administration students in 2024 is significant, with a correlation of rh= 0.785.